Spontaneous recovery, time course, and circadian influence on habituation of the cardiovascular responses to repeated restraint stress in rats - Santos, Carlos E. [UNESP]; Benini, Ricardo [UNESP]; Crestani, Carlos C. [UNESP] (Springer Nature, 2020)
We investigated the spontaneous recovery, time course, and the influence of the time of day on the habituation of the cardiovascular responses with repeated exposure to restraint stress in male rats. Habituation of the corticosterone response to repeated restraint stress was also evaluated. The circulating corticosterone response decreased during both the stress and recovery periods of the tenth session of restraint. Habituation of the cardiovascular responses was identified as a faster return to baseline values of the heart rate (HR) and blood pressure (BP) during the recovery period of the tenth session of restraint. Habituation of the HR and BP was still observed after 10 days of discontinuation of the repeated exposure to restraint stress. However, spontaneous recovery of habituated responses was observed 20 days after the final restraint stress session. Time course analysis revealed decreased HR response during the recovery period of the third restraint session, without further reduction on the fifth, seventh, and tenth sessions. Decreased BP response was identified on the third and fifth sessions, whereas reduced tail skin temperature response was observed only on the fifth and seventh sessions. Regarding the time of day, habituation of the tachycardiac response was identified at the tenth session when repeated restraint stress was performed in the morning and night periods, but not in the afternoon. These findings provided evidence of spontaneous recovery of the habituation of cardiovascular responses to repeated restraint stress. Moreover, cardiovascular habituation was dependent on the number of trials and time of day.
Keywords: Adaptation; Blood pressure; Circadian rhythm; Heart rate; Long term; Time of day